Comparing the effects of blocked and random practice on the closed skill of basketball free throws - Pimentel, Jose Mervin D. 2000-
The contextual interference (CI) effect is a motor learning phenomenon that explains how increasing the level of variation during the practice of a motor skill improves one’s learning of a skill. Random practice is a type of repetition pattern that has a higher CI where skills are practiced randomly instead of in a block. Although the effects of CI on novice learners have been explored, there is a lack of investigation into the effects on experienced athletes. The main objective of this research is to explore the effects of random and blocked practice on a closed skill such as the basketball free throw shot. A repeated measures design was utilized on twelve (12) male high school basketball varsity players whose mean age was 15.75 years. The participants were randomly divided into two groups. A 5-day intervention session was conducted for each of the groups for the first phase. Afterwards, a post-test was gathered after the session. The groups switched practices, and another 5-day intervention was implemented, which was also immediately followed by a second posttest and transfer test. A dependent t-test was used to see if there was a significant difference between the performance results of the groups following the intervention. The study found that there was no significant difference between blocked and random practice in basketball free throws, which implies neither practice intervention is better than the other. The study also showed a decrease in the pretest and posttest performance of the participants